Edward Frost papers - Frost, Edward, 1801-1868.
Correspondence, political, legal, and business records, commissions, appointments, wills, estate and plantation accounts, ledgers, and memorabilia pertaining to Frost's service as district attorney and as states' rights delegate from Charleston to the South Carolina state legislature, and to his interest in the Blue Ridge Railroad Company. Includes legal papers relating to the estates of Thomas Lynch Horry and members of the Blake family. Also includes correspondence concerning the 1st South Carolina Infantry Regiment and the Southern economy during the Civil War. Correspondents include James Hamilton, F. W. Pickens, and members of the Frost family.
Planter, businessman, state legislator, and district attorney for South Carolina.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hamilton, James, -- 1786-1857 -- Correspondence; Horry, Thomas Lynch -- Estate; Pickens, F. W. -- 1805-1869 -- Correspondence; Blake family; Frost family -- Correspondence; Confederate States of America. -- Army. -- South Carolina Infantry Regiment, 1st.; Blue Ridge Railroad Company (South Carolina); Government attorneys -- South Carolina; Plantations -- South Carolina; Railroads -- South Carolina; States' rights (American politics); Confederate States of America -- Economic conditions; South Carolina -- Politics and government -- 1775-1865.; United States -- History -- Civil War, 1861-1865.; Businessmen; Jurists; Legislators -- South Carolina; Plantation owners